First Nations Gaming as a Self-Government Imperative: Ensuring the Health of First Nations Problem Gamblers - Belanger, Yale (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2010)
AbstractAt the end of 2008, there were 17 First Nations casinos operating in Canada. Recent statistics confirm that all are money-making enterprises, and that individual First Nations are using the money to improve social programming and augment infrastructure. What has been overlooked to date is local health: specifically, limited funding was set aside in all Province-First Nations gaming agreements to implement problem-gambling treatment programs for on-reserve residents negatively influenced by the introduction of a casino. This is surprising considering that several studies in Canada and the United States have shown Aboriginal people are more likely to become problem gamblers. This paper argues that by situating a casino in a reserve community, the host community establishes an imperative to treat those negatively affected by ease of access to casino gambling games. To do so is an aspect of self-determination, and a responsibility First Nations assume when selecting casinos as mechanisms of economic development.